MÖ 2. Binyıl Seyitömer Höyük Metal Silahları / Seyitömer Mound Metal Weapons from the 2nd Millennium BC - Rana BAŞKURT USTA (Arkhaia Anatolika)
This study aims to evaluate the metal weapons unearthed from layer IV of Seyitömer Mound, located in Inner Anatolia, which represents the Late Colony and Old Hittite Periods, within the framework of their typological classification and counterparts. Layer IV of the mound was destroyed by fire -as is the case for all other culture levels- and all of the data recovered regarding the level in question, which was excavated horizontally over an extensive area, and found within their contexts, in-situ. This offers an excellent and convenient data source for evaluating the metal items and production materials. The majority of the weapons were found stowed under the floor or the hearth, within the walls. Among these weapon and tool groups, a dagger was found together with a mace head, the like of which has not yet been found in Anatolia. A significant portion of the daggers were uncovered in the structures located at the centre of the mound, around the waist areas of the skeletons belonging to both male and female individuals who possibly failed to escape a fire caused by a hostile invasion. These circumstances may explain the need for personal defence and of the (unusual) finding of citizens armed alike, irrespective of gender. Seyitömer Mound Layer IV weapons consist of daggers, spearheads, flat and lugged axes, pike heads, arrowheads, prongs/pitchforks, and spear wedges. The weapon and tool typology reflect influences within Central Anatolia and Northern Syria/Palestine-Mesopotamia, in addition to the types local to the settlement/original. The evidence points to mutual interaction and influence through information exchange between mining workshops. The tools were produced locally, as proved by the locally discovered ingots, pots, blowpipes, bellows, fanners, and clinkers, along with the many moulds intended for the production of weapons and tools. The settlement at Seyitömer Mound maintained its importance within the mining industry and metals trade since the 3rd millennium BC, due to its strategic location on the transportation routes between the Aegean and the inner regions of Anatolia, and to its proximity to the necessary mineral deposits. The Seyitömer Mound level IV metal weapons inventory, represents a significant portion of the Inner Western Anatolia weapons repertoire, and offers highly valuable and important data regarding the contemporary weapon types and production technologies.